PENGARUH GAYA KEPEMIMPINAN DAN PELATIHAN TERHADAP KINERJA PEGAWAI - SAHRI; SUKRISPIYANTO (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2024)
Many factors affect HR performance, including job satisfaction factors, communication factors, work experience factors, work discipline factors, leadership factors, competency factors, job training factors and work environment factors. The purposes of this study are 1) To find out and analyse the partial effect of leadership on administrative staff performance, 2) To find out and analyse the partial effect of training on administrative staff performance, 3) To find out and analyse the simultaneous effect of leadership and training on administrative staff performance, 4) To find out and analyse between leadership and training which has the most dominant influence on the performance of administrative employees. In this study, the population that became the object of research was administrative staff of 53 respondents. The results of this study indicate that leadership style has no significant effect on administrative staff performance, while training has a partially significant effect on administrative employee performance. From this study it can be seen that leadership style and training variables have a significant simultaneous effect on administrative employee performance. From the results of the study, it can be seen that training has a dominant effect on the performance of administrative employees. Keywords: Leadership Style, Training, Employee Performance